Lipase production from Bacillus safensis VC-6 isolated from the volcanic region of Copahue: optimization and functional genomic insights - Valeria Foronda; Valeria Foronda; Valeria Castellanos; Claudia Hoepfner; Claudia Hoepfner; Daniel Guzmán; Héctor Guzmán; Jerry L. Solis (Frontiers in Microbiology)
Extremophilic microorganisms produce highly stable and industrial-grade enzymes with enhanced performance. Thermostable enzymes, such as lipases that catalyze the hydrolysis and esterification of lipids, are of great industrial interest due to their stability and efficacy under harsh conditions, making them ideal for applications in biotechnology, pharmaceuticals, and cosmetics. Lipase production from various microorganisms is well-studied. However, optimization studies remain limited for lipases sourced from halotolerant bacteria, such as Bacillus safensis strain VC-6, known to grow above 10% (w/v) NaCl and 50°C. The limited research on optimizing these enzymes prevents their widespread adoption in industries requiring high thermostability and solvent tolerance. This study optimized the production of thermostable and halotolerant lipases using the extremophilic strain VC-6, isolated from samples from the Copahue Volcano, Chile. Strain VC-6 was selected from five candidate strains due to its stable growth within simple culture media and positive results in qualitative lipase activity assays. In the initial phases, VC-6 demonstrated superior potential for lipase production. Growth conditions were optimized using a heterotrophic medium supplemented with 2% (w/v) NaCl, 2% (v/v) glycerol, and pH 6 at 37°C. Lipase production was maximized based in the previous medium supplemented with 1% (w/v) yeast extract, 0.5% (w/v) KCl, 3% (v/v) sunflower oil, 2% (v/v) glycerol, and pH 8 at 37°C. Extracellular lipase activity was assessed, and enzyme recovery was facilitated through precipitation methods. Lipase activity was quantified in a batch bioreactor under controlled conditions achieving a maximum enzymatic activity of 12.83 U mL−1 at 16 h of cultivation, correlated with the exponential growth phase of the bacteria. Genetic identification (16S rRNA gene) confirmed that strain VC-6 belongs to the Bacillus genus, sharing 99.93% similarity with Bacillus safensis. Genomic analysis revealed the presence of key genes related to lipase production, including YtpA (phospholipase), LipC (germination lipase), and a thermostable monoacylglycerol lipase. These genes likely explain the observed peaks of enzymatic activity during the fermentation process, with distinct activity observed at different time points. This study highlights the potential of Bacillus safensis strain VC-6 as a promising source of thermostable and halotolerant lipases. The integration of optimized bioprocess conditions and genomic-based understanding establishes a solid groundwork for the future industrial exploitation of these biocatalysts under extreme environmental conditions. The optimization of growth conditions and the identification of critical genes related to lipase production further enhance the potential for scaling up production processes in biotechnological applications.